COMPARATIVE EFFICACY OF MAGNETIC FIELD SEED TREATMENT AND PRIMING IN IMPROVING GROWTH AND PRODUCTIVITY OF OKRA - K. Ziaf1; M. Amjad; M. A. Ghani; I. Ahmad; M. Ayub; M. Sarwar; Q. Iqbal; M. A. Nawaz (Journal of Animal and Plant Sciences, 2022)
Seed priming (halo- and hydro-priming) and magnetic seed treatments have been used to invigorate seeds. Primed seeds cannot be stored for long duration due to start of gemination processes, although dried to initial seed moisture content at the end of lag phase of germination. On the other hand, magnetic seed treatment invigorates the seeds without starting germination processes and so considered safe for storage of seeds. The comparative evaluation as well as their impact on various physiological aspects of okra plant has been scarcely evaluated. A field experiment was conducted to compare the impact of seed priming (hydro-priming and halo-priming) and magnetic field seed treatments, on growth, photosynthesis related attributes and yield of two okra cv. Sabz Pari and Super Green during summer 2016. Seeds of both cultivars, primed in water (hydro-priming), salt solution (halo-priming using NaCl 1%, ZnSO4 0.1%, CuSO4 0.1%, H3BO3 1%, KNO3 1% and 2%), or exposed to magnetic field of 100 or 200 mT for 10 or 20 minutes, were sown in field according to randomized complete block design under factorial arrangements. Results revealed that magnetic field seed treatment, specifically 100 mT for 20 minutes, improved emergence (25-34% over control), seedling fresh and dry weight, leaf weight, pod length, number of fruits per plant and fruit yield per plant (27-38% over control). Chlorophyll contents of both okra cultivars were highest in response to seed priming with 1% KNO3. Transpiration rate and net photosynthetic rate of both okra cultivars were also high for plants grown using 100 mT for 20 minutes treated seeds of both cultivars. While, sub-stomatal conductance of cv. Sabz Pari and Super Green was highest in response to 100 mT for 10 minutes and 1% NaCl, respectively. However, water use efficiency of Sabz Pari and Super Green was highest for plants raised using seeds primed in 1% KNO3 and 1% H3BO3, respectively. It may be inferred that pre-sowing magnetic field treatment of seed (100 mT for 20 minutes) can be effectively used to improve okra crop stand establishment, growth and yield followed by seed priming in 1% KNO3. Moreover, magnetic seed treatment, being less damaging to seed, is more suitable than priming; the later one decreases storage life of seed.
Keywords: Abelmoschus esculentus; Halopriming; Hydropriming; Magnetic field seed treatment; Seedling traits; Gas exchange attributes